INDONESIAN EFL TEACHERS’ PERCEPTIONS TOWARD ICT INTEGRATION FOR LANGUAGE TEACHING IN REMOTE AREAS - Muhaji, Uun; Muzammil, Lasim; Andy ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
Considering the challenges in integrating Information and Communication Technology (ICT) into language teaching in Indonesia’s remote areas, the perspectives of English as a Foreign Language (EFL) teachers on this development have not been thoroughly investigated. This study aims to address questions regarding the extent of their awareness of ICT advancements, their integration of ICT into English language teaching (ELT), and their concerns about their ICT skills and knowledge. Data were collected through an online survey of 50 EFL teachers working in remote areas of West Kalimantan and East Nusa Tenggara. The survey included seven closed-ended and four open-ended questions focusing on their attitudes toward ICT development in language teaching and their adoption of ICT practices. The results indicate that the participants hold positive perceptions of ICT development in language teaching and, despite various limitations, make efforts to integrate ICT into their teaching practices. However, they also expressed significant concerns about their skills and knowledge of ICT. These findings highlight the need for supporting facilities and targeted training to enhance ICT integration in language teaching for EFL teachers in remote areas.